Novel design of triple-bands EBG - M. K. Abdulhameed; M. S. Mohamad Isa; Z. Zakaria; I. M. Ibrahim; Mowafak K. Mohsen; Ahmed M. Dinar; Mothana L. Attiah (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
This paper presents a novel design for a triple band electromagnetic band gap (EBG) structures that provides three band gaps, with operating frequency of below 10 GHz, while the ordinary mushroom like EBG structure gives only one band gap. Complexity reduction (reduce the number of unit cells and Vias) was achieved by replacing each four cells of the Mushroom like EBG by the one of double slotted type EBG (DSTEBG) or triple side slotted EBG (TSSEBG). The Mushroom like EBG was further modified by increasing its size and inserting the slots to gain more capacitance and inductance which resulted into triple band stop.The new designs wer compared with bandwidths expressed by other EBGs and -20 dB cut-off frequencies. The size of EBG element and the gap between EBG elements, and slot width were investigated to analyse their effect on the transmission response. The structures were designed from 2.54 mm Rogers RT/Duroid 6010 substrate with relative permittivity of 10.2 and loss tangent of 0.0023. Among the investigated EBGs, the single band mushroom like EBG and the triple band of the TSSEBG demonstrated better bandwidth and lower resonance frequency performance, whereas the DSTEBG showed larger bandwidth for the first and third band. The proposed EBGs could be useful in the antenna design and other microwave circuits.